Oxalic Acid Production of Banana Peel (Musa Textilia) Through Optimum Temperature and Time with Alkaline Method - Yuni Kurniati; Irvan Adhin Cholilie; Paramita Setyaningrum; Fahimah Martak; Dewi Gita Anggraini; Viqorul Ahmad Haryadi (Universitas Djuanda, 2023)
The chemical compound has the formula H2C2O4 is oxalic acid. Every year especially, the industrial sector in Indonesia requires oxalic acid made, which increases annually. Oxalic acid is valuable because it may be used to clean (rust remover), make colors, protect metals from corrosives, and other things. Alkaline melting is one way for creating oxalic acid from cellulose-containing materials. Other methods include hydrolysis, CaCl2 precipitation, and acidification using H2SO4. In Indonesia, cellulose-containing materials are widely available. Banana peels are one of the substances that contain cellulose. In addition to identifying the properties of oxalic acid produced using the alkaline smelting process, this study attempts to find the best temperature and duration for producing oxalic acid from discarded banana peels. The ideal conditions include a temperature of 60°C, a period of 60 minutes, and a yield of 5.42%. Oxalic acid from banana peel waste has the properties of having a melting point, hydroxyl, C=C, C-O, and C-H group absorption at a wave number of 104.6 oC, 3422.06 cm-1, 1682.48 cm-1, 1103.42 cm-1, and 666.36 cm-1 respectively. Based on the strain vibration results from the FTIR test and melting point test.